Problems of Nonlinear Mechanics and Physics of Materials - Andrianov, Igor V.; Manevich, Arkadiy I.; Mikhlin, Yuri V.; Gendelman, Oleg V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents contributions on the current problems in a number of topical areas of nonlinear dynamics and physics, written by experts from Russia, Ukraine, Israel, Germany, Poland, Italy, the Netherlands, the USA, and France. The book is dedicated to Professor Leonid I. Manevitch, an outstanding scholar in the fields of Mechanics of Solids, Nonlinear Dynamics, and Polymer Physics, on the occasion of his 80th birthday.
Asymptotic higher-order dynamic model for transient waves in heterogeneous -- Analysis of the beating states in the system of nonlinearly coupled parametrically forced oscillators -- Is energy localization possible in the conditions of non-local acoustic vacuum? -- Phase dynamics of tunneling intrinsic localized modes in weakly coupled nonlinear chains and correspondence between classical and quantum particles -- Non-linear beatings as non-stationary synchronization of weakly coupled autogenerators.
Keywords: Mechanics, Applied; Solids; Materials -- Analysis; Mechanics; Solid Mechanics; Characterization and Analytical Technique; Classical Mechanics